USM GETS NEW REGISTRAR – PROF. DR. ABD. AZIZ TA JUDDIN - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 6 January 2016 – Professor Dr. Abd. Aziz bin Tajuddin, 60, has been appointed as the new registrar at Universiti Sains Malaysia (USM) for two years effective from January 1, 2016.